Climate capacity in medium-sized German cities: (how) do smaller municipalities implement mitigation and adaptation policies? - Peter Eckersley; Antje Otto; Wolfgang Haupt; Kristine Kern (npj Climate Action)
Abstract Although research has begun to examine local mitigation and adaptation approaches in parallel, it has tended to focus on leading cities and adopt large-N approaches that focus on published climate plans. We know little about whether smaller local governments are able to address these twin challenges simultaneously, or whether and how they are implementing their planned policies. Drawing on analysis of 194 German cities, supplemented by fieldwork interviews in ten of these municipalities, we find that smaller cities are focusing increasingly on both mitigation and adaptation at the institutional level. However, concerns remain about implementation and the long-term development of infrastructure projects. Moreover, there is a risk that our knowledge of local climate policy, much of which is based on climate planning documents, may be distorted because municipalities are incentivised to produce highly ambitious and unrealistic plans, and often rely heavily on external experts to draft these documents.